Breathing environment: Exploring the feasibility and efficacy of personalized, light-guided slow breathing while performing two computer tasks in a simulated office environment - Markus Canazei; Luis Glenzer; Siegmund Staggl; Verena Dresen; Johannes Weninger; Elisabeth Margarete Weiss (Computers in Human Behavior Reports)
Background: Screen-based tasks are known to significantly affect stress levels and well-being. Slow Breathing (SB) is a promising intervention to reduce stress by increasing parasympathetic nervous system activity. This study investigated the feasibility and immediate stress-reducing effects of light-guided SB during two computer-based tasks in a simulated office environment. Methods: Eighty young, healthy adults participated in a randomized crossover study with two study conditions while performing computer tasks: a personalized, light-guided SB and an artificial office lighting and a control condition with artificial office lighting only. Participants completed an attention task (Psychomotor Vigilance Task) and a decision task (Balloon Analogue Risk Task) in both conditions. Measurements included heart rate variability via root mean square of successive differences (RMSSD), subjective stress levels, and usability metrics. Results: Light-guided SB showed a significant increase in RMSSD for both tasks. Perceived stress levels were also significantly lower after performing the decision task with SB. From a performance perspective, SB resulted in reduced attentional performance and had no effect on decision making. Usability ratings complemented these findings, showing higher perceived distraction with light-guided SB, but hedonic quality ratings were more favourable. Discussion: Additional light-guided SB, although costly in cognitive resources, effectively promotes physiological self-regulatory processes in situ in two cognitive tasks and also reduces perceived stress in a higher executive cognitive task. These findings highlight the potential of SB for occupational stress management without disrupting work flow.